Analysis of Factors Influencing Millennial Consumers' Decision in Buying Halal Cosmetics - Jailani, Novalini; Susminingsih; Adinugraha, Hendri Hermawan; Kari, Fatimah; Muhammad, Adib (Tribakti: Jurnal Pemikiran Keislaman, 2024)
The market potential of the halal cosmetics is currently very promising and the use of cosmetics among millennials is increasing. Therefore, the purpose of this research is to analyze the factors that impact millennial consumers' decisions to buy halal cosmetics. This study analyzes whether factors such as halal awareness, halal certification and religiosity are able to influence millennial consumers' decisions in buying halal cosmetics with purchase intention as a mediating variable. In this study, a quantitative method using survey research was applied. The method of sampling utilized in this investigation was incidental sampling, where the study sample was as many as 185 millennial consumers in Central Java province with the condition that they were millennials born between 1981 to 1996 and had bought halal cosmetic products. Data collection techniques use online questionnaires in the form of Google forms that are disseminated through social media, such as Instagram and Whatsapp. The data analysis method used is SEM-PLS by using SmartPLS 3.2.9 software. The results of this study found that the variables of halal awareness, halal certification and religiosity have a positive and significant influence on millennial consumers' decisions in buying halal cosmetics. Consumer purchase intent was able to mediate the relationship between variables of halal awareness, halal certification, religiosity and purchase decisions significantly. The findings of this research can be used as consideration for manufacturers or marketers of cosmetic products to pay attention to religious aspects in promoting their products. Those in the cosmetics industry who are trying to reach millennials might think about getting their products halal certified. Especially in the context of advertising. One marketing strategy that has shown success is labeling items as "halal certified."